Behind the veil voices of moro women - Rimban, Luz.; Bonoan, Jam.; Maglipon, Jo-Ann.; Diokno, Ma. Socorro; Philippine Center for Investigative Journalism (Quezon City The Center, 1998)
A documentary on the dilemma faced by the Bangsamoro women. War is bloody and costly. And peace does not always right old wrongs. Through these uncertainties, the anchor that keeps the Bangsamoro woman strong is her religion. The veil is her commitment to Islam and symbolizes submission to the teaching of Koran.
Produced by the Women's Desk of the Philippine Center for Investigative Journalism.
Keywords: Moro National Liberation Front; Bangsamoro Women Foundation for Peace and Development; Moro Islamic Liberation Front; Muslim women -- Philippines -- Mindanao; Mindanao -- History. -- Autonomy and independent movements